PENGARUH INOVASI PRODUK DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP CITRA PERUSAHAAN - Sungandi, Vincent Meidian; Moko, Wahdiyat (Jurnal Kewirausahaan dan Inovasi, 2023)
This research aims to identify the effect of product innovation & Corporate Social Responsibility (CSR) on the corporate image of PT Goto Gojek Tokopedia Tbk. The respondents of this quantitative case study are 100 university students. The data was harvested from Likert-scaled questionnaires & was analyzed using multiple linear regression. The results of the analysis indicate that product innovation (X1) & Corporate Social Responsibility (X2) simultaneously have positive & significant effects on corporate image (Y) as the F statistics is greater than the F table with 49.760>3.09, & the F significance value of 0.000 is smaller than 0.05 (5%). The results of the t test show that the t statistics is greater than the t table with 4781>1.90, or the sig. t (0.000) is smaller than the α value (0.05). This means that Corporate social responsibility (X2) positively & significantly affects corporate image (Y). The result of the t test for product innovation is that the t statistics is greater than the t table with 5.341>1.90, or the sig. t (0.000) is smaller than the α value (0.05). This means that product innovation (X1) positively & significantly influences corporate image (Y).